Current treatment of cholinesterase inhibitors poisoning: misconceptions and need for updated Peruvian guidelines - Virú Loza, Manuel André (2015)
Millions of cases of cholinesterase inhibitors poisonings occur in the world and thousands of deaths by these substances are reported. Our country is not different scenario. The most useful treatment regimen is currently under research and some extensively used measures are on debate. The current trend is aggressive treatment as severe life-threatening adverse effects by drugs like atropine are very rare. In Peru there is no active research on this issue and only an organophosphate and carbamate poisoning in children treatment guide by the Ministry of Health in 2005 is available. It is urgent to update these guidelines, since they contain concepts that in some cases have radically changed due to current knowledge. The aim of this review is to briefly expose the most relevant updated information on treatment of these poisonings, to suggest evaluation of the mentioned guidelines, and to call attention of the Peruvian Ministry of Health authorities to develop guidelines for adults.